(untitled) (Journal of the College of Basic Education, 2022)
The Mongol Empire developed remarkably and within a short period, due to many reasons, foremost of which is the intensification and development of the intelligence apparatus, starting with planting eyes in all countries, ending with the allocation of a system made up of a group of individuals who are very intelligent and able to delude, and the accumulated experiences of previous countries were They have a great role in this, and at the forefront of which is China, who were affected by them, and this was reflected in the development of the espionage system, which had great credit for extending the Mongol influence over a vast country extending from Mongolia to the Islamic world. Not to mention the factors of weakness experienced by the neighboring countries, which allowed this empire to exploit all of this for its benefit, and thus resulted in the fall of the greatest Arab state known in history, the Abbasid state, which spanned for five centuries (132-656 AH / 750-1258 AD). Espionage is one of the oldest occupations practiced by man in the organized human societies since the dawn of creation. His practice represented an urgent need for his innate instinct to acquire knowledge and to attempt to extrapolate the unknown and reveal his secrets that may form And many of them have been able to dig their names in the memory of history, and that the espionage has appeared in many nations and peoples and from the Among these peoples are the Mongols Who used it to obtain information for the expansion and occupation and the extension of military influence on the countries and territories they annexed to their vast empire, we have decided to highlight this task, which the Mongols counted priorities of their work and military efforts to occupation and hegemony wiped out the world then.